2006
DOI: 10.1097/01.blo.0000246539.57198.29
|View full text |Cite
|
Sign up to set email alerts
|

THA Performed using Conventional and Navigated Tissue-preserving Techniques

Abstract: Less invasive methods of performing total hip arthroplasty have been considered controversial after increased complication rates and component malpositioning were reported. A new method of performing total hip arthroplasty through an incision in the superior capsule, posterior to the abductors and anterior to the posterior capsule, was developed with the aim of producing a technique that maintained the joint stability of the transgluteal exposure and the rapid abductor recovery of the posterior exposure. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 21 publications
3
37
0
3
Order By: Relevance
“…As a result, we found no difference in the operative time and blood loss between the two groups. The operation time and blood loss with the surgical guide were comparable to those reported for conventional and navigated THAs [12,18,20,26] (Table 3). Two previous reports suggest the navigation systems with an optical sensor take an additional 15 to 46 minutes of operating time over conventional procedures [1,30].…”
Section: Discussionsupporting
confidence: 62%
“…As a result, we found no difference in the operative time and blood loss between the two groups. The operation time and blood loss with the surgical guide were comparable to those reported for conventional and navigated THAs [12,18,20,26] (Table 3). Two previous reports suggest the navigation systems with an optical sensor take an additional 15 to 46 minutes of operating time over conventional procedures [1,30].…”
Section: Discussionsupporting
confidence: 62%
“…Minimally invasive THA involves a modified surgical dissection that uses internervous planes while minimising any tendon or muscle trauma during the exposure [10,19,28,29]. High-technology computer navigation can be used for correct positioning of the components given the decreased visualisation of minimally invasive surgery [32,40]. Choice of implants and cementing techniques was highly variable across studies when reported.…”
Section: Discussionmentioning
confidence: 99%
“…For all hips, a less invasive approach, the superior capsulotomy [13], was performed with the patient in the lateral decubitus position. The cups were impacted using an angled impactor and all the operations were performed by one surgeon (SBM).…”
Section: Methodsmentioning
confidence: 99%